A Woodland Biface Cache from the Ranch Dash 3 Site, 47-MO-828, Monroe County, Wisconsin. (1st October 2016) - Olsen, Tyler J.; Woods, Alexander D.
Abstract : Archaeological investigations during the 2014 field season at the Fort McCoy military installation in Wisconsin encountered a lithic artifact cache at the Ranch Dash 3 site (47-MO-828). Radiocarbon dating of charcoal samples collected from direct association with the feature returned dates associated with the transition from the Early Woodland period into the Early Middle Woodland period. The Ranch Dash 3 cache was recovered in the course of a controlled professional investigation, and while these blanks may have been cached for future biface production, they were most likely left behind because they were not of sufficient quality to merit further transport.